THE PHENOMENON OF RUMORS AMONG GRADUATE STUDENTS AT THE UNIVERSITY OF DEBRECEN IN HUNGARY FROM THEIR PERSPECTIVE. - Abdullah, Sajeda (Humanities Journal of University of Zakho, 2025)
This research aims to study the phenomenon of rumors among graduate students at the University of Debrecen in Hungary from their perspectives, focusing on the nature of rumors, the reasons for their spread, and their impact on the academic, psychological, and social environment of students. The researcher used the descriptive-analytical approach, and relied on the scale (Al-Sunaid Al-Mari et al., 2012), where the number of items was (10) and was distributed electronically to a random sample of master's and doctoral students in various disciplines. The results of the study showed that rumors are a noticeable phenomenon in the university environment, and are often spread through social media and messaging applications. It also became clear that the topics most frequently raised by rumors are related to scholarships, personal relationships, and academic courses. Most participants indicated that the main reason for the spread of rumors is the lack of official information and poor communication between students and university administration, according to each item individually. It is not necessary for the results to be good and for there to be rumors, and it is possible that there are no rumors, such as political, religious, social, etc. The study recommended the necessity of strengthening official communication channels between the university and students, organizing awareness campaigns about the dangers of rumors and their negative effects on individuals and the university community, in addition to developing critical thinking skills among students to limit the impact of rumors on them.